EFIKASI DAN EFEKTIVITAS FORMULASI DAUN MELADA (Piper colubrinum Link) SEBAGAI ATRAKTAN HAMA LALAT BUAH (STUDI KASUS PERTANAMAN CABAI) - Feby, Febrina; Sepianto, Sepianto; Julianto, Bayu; Hidayat, Hidayat; Januarti, Putri; Simamora, Cico Jhon Karunia (Jurnal Agroteknologi, 2024)
Fruit flies ( Bactrocera spp.) represent a group of Plant Pests that can inflict both qualitative and quantitative losses. The utilization of chemical pesticides and the scarcity of Methyl Eugenol continue to pose significant challenges in agriculture. The abundant availability of Melada plants presents an opportunity for the development of an economically viable and environmentally friendly biological attractant. Encapsulation technology based on Maltodextrin and Gum Arabic (MD-GA) formulated with powdered simplicia of Melada leaves F1(02:10), F2(05:10), F3(10:10), and F4(12:10) is employed to enhance the slow-release resistance of volatile compounds. The surface oil content of the four formulations ranges from 0.3% to 9.6%. The encapsulation efficiency value for the four formulations ranges from 70% to 85%. The loading capacity value ranges from 0.7% to 1.3%. The yield value of microcapsule characteristics ranges from 63% to 82%. Morphological analysis reveals a decrease in the number of particles along with the combination of treatment formulations. The size of the microcapsules for the four formulations falls within the range of 201.2 µm–252.6 µm. The effectiveness of the resulting attractant can lure 19-185 fruit flies. The diversity of the fruit fly pest population obtained includes the Bactrocera umbrosa and Bactrocera melastomatos species. The total value of the best formulation for the four treatments ranged from 0.3% to 0.5%. The optimization of the best biological attractant application with high development potential lies in the encapsulation formulations F3 and F4.